2006
DOI: 10.1088/1126-6708/2006/11/015
|View full text |Cite
|
Sign up to set email alerts
|

On the thermodynamic geometry of BTZ black holes

Abstract: We investigate the Ruppeiner geometry of the thermodynamic state space of a general class of BTZ black holes. It is shown that the thermodynamic geometry is flat for both the rotating BTZ and the BTZ Chern Simons black holes in the canonical ensemble. We further investigate the inclusion of thermal fluctuations to the canonical entropy of the BTZ Chern Simons black holes and show that the leading logartithmic correction due to Carlip is reproduced. We establish that the inclusion of thermal fluctuations induce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
147
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 26 publications
3
147
0
1
Order By: Relevance
“…The Weinhold and Ruppeiner geometries have been analyzed in a number of black hole families to study phase space, critical behavior, and stability properties [12][13][14][15][16][17][18][19][20][21][22]. In some particular cases, it was found that Weinhold and Ruppeiner geometries carry information about the phase transitions structure.…”
Section: Introductionmentioning
confidence: 99%
“…The Weinhold and Ruppeiner geometries have been analyzed in a number of black hole families to study phase space, critical behavior, and stability properties [12][13][14][15][16][17][18][19][20][21][22]. In some particular cases, it was found that Weinhold and Ruppeiner geometries carry information about the phase transitions structure.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Bañados, Teitelboim and Zanelli (BTZ) came with surprising result that three dimensional gravity with a negative cosmological constant has a black hole solution [59]. BTZ black holes provide a good understanding of certain central issues like black hole thermodynamics [60][61][62], quantum gravity, string and gauge theory and more importantly the AdS/CFT conjecture [63,64]. Furthermore, BTZ solutions perform a crucial role in improving our perception of gravitational interaction in low dimensional spacetime [65].…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensional solutions of black holes and magnetic solutions have been studied by many authors [50][51][52][53][54][55][87][88][89][90][91][92][93]. This tremendous interest in these solutions is due to fact that three dimensional solutions contribute fundamentally to conceptual issues of astrophysical subjects such as black holes thermodynamics [94][95][96]. In addition, in context of quantum gravity and string theory, also due to AdS/CFT correspondence, these theories play an undeniable important role in describing different phenomena specially in low dimensional spacetime [97][98][99].…”
Section: Introductionmentioning
confidence: 99%